2020
DOI: 10.1016/j.clineuro.2020.106112
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic presentations of COVID-19: Risk factors for mortality

Abstract: Objective We aim to characterize the incidence, risk for mortality, and identify risk factors for mortality in patients presenting with hemorrhage and COVID-19. Methods This retrospective cohort study included a cohort of patients admitted to one of three major hospitals of our healthcare network including, an academic medical center and comprehensive stroke center, which accepts transfers for complex cases from eight community hospitals, during March 1 to May 1, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 19 publications
2
76
1
Order By: Relevance
“…All 18 studies were included in the meta-analysis to calculate the global prevalence of hemorrhagic stroke in COVID-19 patients and the frequency of symptoms leading to hospital admission 32 49 . Data from nine studies were included to calculate the mortality rate of hemorrhagic stroke in COVID-19 patients 32 , 33 , 35 37 , 40 , 45 , 48 , 49 , while the other nine studies did not report relevant data. The 18 studies and the prevalence of hemorrhagic stroke reported in each of them are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All 18 studies were included in the meta-analysis to calculate the global prevalence of hemorrhagic stroke in COVID-19 patients and the frequency of symptoms leading to hospital admission 32 49 . Data from nine studies were included to calculate the mortality rate of hemorrhagic stroke in COVID-19 patients 32 , 33 , 35 37 , 40 , 45 , 48 , 49 , while the other nine studies did not report relevant data. The 18 studies and the prevalence of hemorrhagic stroke reported in each of them are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our review documented a total of 18 studies reporting about imaging features of 135 COVID-19 patients with ICH. 12,18,21,22,26,48,56,57,59,65,[71][72][73][74][75][76][77] Eight studies were presented as single case reports or as case series. 48,59,[71][72][73][74][75]77 Another eight studies were conducted as retrospective studies reporting on neuroimaging findings of ICH patients.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…The novel coronavirus disease 2019 (COVID-19) is a global pandemic with international concern [ 1 ]. SAH is a devastating disease [ 2 ], which accounts for approximately 5–10 % of strokes [ 2 ] Several case report about the SAH and COVID-19 infection have been reported [ [3] , [4] , [5] , [6] ], but three reviews about the interaction between COVID-19 and the central nervous system have been recently published, but the occurrence of SAH in patients with Covid-19 infection has not been mentioned in these reviews [ [7] , [8] , [9] ]. There is limited knowledge on the SAH following COVID-19 at present.…”
Section: Introductionmentioning
confidence: 99%